1984
DOI: 10.1289/ehp.8455205
|View full text |Cite
|
Sign up to set email alerts
|

Lung surfactant.

Abstract: Aspects of pulmonary surfactant are reviewed from a biochemical perspective. The major emphasis is on the lipid components of surfactant. Topics reviewed include surfactant composition, cellular and subcellular sites as well as pathways of biosynthesis of phosphatidylcholine, disaturated phosphatidylcholine and phosphatidylglycerol. The surfactant system in the developing fetus and neonate is considered in terms of phospholipid content and composition, rates of precursor incorporation, activities of individual… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
16
0

Year Published

1987
1987
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 45 publications
(17 citation statements)
references
References 334 publications
(304 reference statements)
1
16
0
Order By: Relevance
“…PA de novo biosynthesis utilizes dihydroxyacetone phosphate (DHAP) derived from glucose or glycogen that is then processed into PA by two different pathways both of which are active in the lung [30, 31]. It was shown that fetal type II cell precursors accumulate significant amounts of glycogen that are used as a carbon source, providing chemical energy and serving as an important precursor for PA and surfactant synthesis [32].…”
Section: Synthesis and Regulation Of Surfactant Phospholipidsmentioning
confidence: 99%
See 4 more Smart Citations
“…PA de novo biosynthesis utilizes dihydroxyacetone phosphate (DHAP) derived from glucose or glycogen that is then processed into PA by two different pathways both of which are active in the lung [30, 31]. It was shown that fetal type II cell precursors accumulate significant amounts of glycogen that are used as a carbon source, providing chemical energy and serving as an important precursor for PA and surfactant synthesis [32].…”
Section: Synthesis and Regulation Of Surfactant Phospholipidsmentioning
confidence: 99%
“…Endogenous glucocorticoids directly affect fetal lung maturation via glucocorticoid receptors identified in the type II alveolar cells [8, 247, 248]. Glucocorticoids also exert stimulatory effects on regulatory enzymes (CTP, CPT, PAP, glycerophosphate phosphatidyltransferase and phosphatidylglycerophosphatase) involved in phospholipid biosynthesis [9, 31]. Thyroid hormone also accelerates lung maturation and increases surfactant PC biosynthesis [8, 31, 249].…”
Section: Modulators Of Surfactant Production In Lung Diseasementioning
confidence: 99%
See 3 more Smart Citations